The Internal Determinants of Cost Efficiency in Jordanian Islamic Banks - Sindiani, Qusai; Albadreen, Abdullah (Jordan Journal of Islamic Studies, 2024)
The study aimed to identify the internal factors affecting cost efficiency in Jordanian Islamic banks for the period (2012-2021). The study expressed cost efficiency through the expenses-to-revenue ratio as a dependent variable. The independent variables were the return-on-assets ratio, return-on-deposits ratio, capital adequacy ratio, ownership rights-to-assets ratio, fixed capital cost ratio, labor costs, and bank size. The study used a descriptive-analytical approach, where data stationarity was tested, and the Autoregressive Distributed Lag Model (ARDL) was employed to determine the effect of independent variables on the dependent variable. The study found a statistically significant positive impact of the capital adequacy ratio, ownership rights-to-assets ratio, and fixed capital cost ratio. It detected a negative effect of labor costs and found no statistically significant differences in the return-on-assets ratio, return-on-deposits ratio, and bank size on cost efficiency in Jordanian Islamic banks. The study recommended working to enhance cost efficiency by improving resource distribution, enhancing technical proficiency, and refining the banks’ inputs, thus increasing their competitiveness and profitability.